Protocol for a randomized controlled trial: exercise-priming of CBT for depression (the CBT+ trial) - Jacob D. Meyer; Shania J. E. Kelly; John M. Gidley; Jeni E. Lansing; Seana L. Smith; Sydney L. Churchill; Emily B. K. Thomas; Simon B. Goldberg; Heather C. Abercrombie; Thomas A. Murray; Nathaniel G. Wade (Trials, 2024)
Abstract Background Depression is a leading cause of disability worldwide, and treatments could be more effective. Identifying methods to improve treatment success has the potential to reduce disease burden dramatically. Preparing or “priming” someone to respond more effectively to psychotherapy (e.g., cognitive behavioral therapy [CBT]) by preceding sessions with aerobic exercise, a powerful neurobiological activator, could enhance the success of the subsequently performed therapy. However, the success of this priming approach for increasing engagement of working mechanisms of psychotherapy (e.g., increased working alliance and behavioral activation) has yet to be formally tested. Methods The CBT + trial will be a parallel-arm randomized controlled trial that will recruit 40 adult participants with DSM-5 diagnosed depression (verified with clinical interview) via referrals, mass emails, local flyers, and social media posts. Participants will be randomized to an ActiveCBT or CalmCBT condition. The ActiveCBT group will receive an 8-week CBT intervention primed with 30 min of moderate-intensity aerobic exercise (cycling on a stationary bike at a 13 rating of perceived exertion). The CalmCBT group will receive the same 8-week CBT intervention while resting for 30 min before CBT (i.e., cycling vs no cycling is the only difference). The primary outcome measures will be mean working alliance (assessed with the client version of the Working Alliance Inventory—Short Revised) and mean behavioral activation (self-reported Behavioral Activation for Depression Scale) recorded at each of the 8 therapy sessions. Secondary outcomes include evaluation of state anhedonia and serum brain-derived neurotrophic factor before the active/calm conditions, between the condition and therapy, and after the therapy. Additional exploratory analyses will evaluate group differences in algorithm-generated ratings of therapist-participant interactions via the Lyssn platform. Discussion The novel approach of priming CBT with moderate-intensity aerobic exercise evaluated in a randomized controlled trial (CBT + trial) has the potential to demonstrate the usefulness of exercise as an augmentation strategy that improves working mechanisms of therapy and overall treatment outcomes for adults with depression. Trial registration ClinicalTrials.gov NCT06001346 . Registered on August 21, 2023.